Islamic Boarding School (Pondok Pesantren) , Independent And Community Empowerment - Dwi Purwoko (Populis : Jurnal Sosial dan Humaniora, 2022)
Implementation of the learning system at Islamic Boarding Schools (Pondok Pesantren – commonly called in Indonesia) usually leaves an imprint in the memory of the students who in turn will make it perspective that can be applied in their everyday lives, both in their ways of thinking and when they make good deeds blessed by the God. In addition, the Islamic Boarding School that plays strategic roles and has long been rooted in the Indonesian society has its own force in arousing the spirit and passion of the students to advance towards more prosperous and independent life. The values learned in the school, in particular its values of self-reliance, have encouraged the santri to practice these values in the society. Coming from such background, this research aims to provide an overview of the boarding schools that teach independent life to the students who in turn, when they graduate, they may empower the community in which they live.Penerapan sistem pembelajaran di Pondok Pesantren biasanya meninggalkan jejak dalam ingatan para santri yang pada gilirannya akan menjadikannya cara pandang yang dapat diterapkan dalam kehidupan sehari-hari, baik dalam cara berpikirnya. dan ketika mereka melakukan perbuatan baik yang diberkati oleh Tuhan. Selain itu, Pondok Pesantren yang memiliki peran strategis dan telah lama mengakar dalam masyarakat Indonesia memiliki kekuatan tersendiri dalam membangkitkan semangat dan gairah santri untuk maju menuju kehidupan yang lebih sejahtera dan mandiri. Nilai-nilai yang dipelajari di sekolah, khususnya nilai-nilai kemandirian, telah mendorong santri untuk mengamalkan nilai-nilai tersebut di masyarakat. Berangkat dari latar belakang tersebut, penelitian ini bertujuan untuk memberikan gambaran tentang pesantren yang mengajarkan kehidupan mandiri kepada para santrinya yang pada gilirannya kelak ketika mereka lulus dapat memberdayakan masyarakat di mana mereka tinggal.